CSF otorrhea as a late complication of ear surgery - Ferreira, Joana Maria Soares (2022)
We present the case of a cerebrospinal fluid leak and a meningoencephalocele as a late complication of ear surgery, manifested with cerebrospinal fluid otorrhea. The objective is to alert to this rare condition, its clinical manifestations, diagnosis and treatment, as well as the potential complications of its early non-recognition. We describe the case of an 81-year-old man, with a past history of ear surgery (20 years ago), with one month history of otorrhea, refractory to medical treatment. Objectively, he had colorless, medium-output otorrhea, which increased with valsalva maneuver, and a polypoid lesion in auditory canal. The otorrhea test strip was positive for glucose. Ear CT and cranial MRI revealed the presence of a meningoencephalocele in the tympanic cavity. The patient was successfully treated with surgery using a combined multidisciplinary approach that the authors describe.